Preformulation Characterization and the Effect of Ionic Excipients on the Stability of a Novel DB Fusion Protein - Jain, Akshay (J Pharm Sci, 2020)
Shigella ssp cause bacillary dysentery (shigellosis) which has high global morbidity in young children and the elderly. The virulence of Shigella relies upon a type III secretion system (T3SS) which injects host altering effector proteins into targeted intestinal cells. The Shigella T3SS contains two components, invasion plasmid antigen D (IpaD) and invasion plasmid antigen B (IpaB), that were previously identified as broadly protective antigens. When IpaD and IpaB were co-expressed to give the DB fusion (DBF) protein, vaccine efficacy was further improved. Biophysical characterization under various pH conditions showed that DBF is most stable at pH 7 and 8 and loses its conformational integrity at 48 and 50 °C respectively. Forced degradation studies revealed significant effects on the secondary structure, tertiary structure and conformational stability of DBF. In the presence of phosphate buffers as well as other anionic excipients, DBF demonstrated a concentration dependent conformational stabilization. Molecular docking revealed potential polyanion binding sites in DBF that may interact with phytic acid. These sites can be exploited to stabilize the DBF protein. This work highlights potential destabilizing and stabilizing factors, which not only improves our understanding of the DBF protein but helps in future development of a stable Shigella vaccine.